Gene drive: what is possible at the population level with currently-available molecular components? - Marshall, John (Henry Stewart Talks, 2018)
Mathematical Modeling of Gene Drive, Medea, Toxin-antidote-based underdominant systems, Reciprocal chromosomal translocations, Spatially-structured modeling frameworks, Confineable homing-based gene drive systems, Potential for invasive homing-based systems following field trials